2020
DOI: 10.1021/acsomega.0c00205
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of Human Uridine-5′-diphosphate-glucuronosyltransferase 1A6 Reveals Insights into Factors Influencing Substrate and Cosubstrate Binding

Abstract: The elimination of numerous endogenous compounds and xenobiotics via glucuronidation by uridine-5′-diphosphate glycosyltransferase enzymes (UGTs) is an essential process of the body’s chemical defense system. UGTs have distinct but overlapping substrate preferences, but the molecular basis for their substrate specificity remains poorly understood. Three-dimensional protein structures can greatly enhance our understanding of the interactions between enzymes and their substrates, but because of the inherent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…However, it is also worth noting that there is an experimental evidence indicating the importance of H34 in catalyzing O-glucuronidation reaction, that concluded the need for further investigations to elucidate its function [ 70 ]. It is also likely that binding affinities of the putative ligands may be biased by the template substrate specificities used for homology modelling as it was seen in case of UGT1A6 [ 71 ]. Since UGTs also participates in glucosidation, residues offering specificity for glucuronidation or glucosidation in N-terminal domain may also be biased by the template used for homology modelling(e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also worth noting that there is an experimental evidence indicating the importance of H34 in catalyzing O-glucuronidation reaction, that concluded the need for further investigations to elucidate its function [ 70 ]. It is also likely that binding affinities of the putative ligands may be biased by the template substrate specificities used for homology modelling as it was seen in case of UGT1A6 [ 71 ]. Since UGTs also participates in glucosidation, residues offering specificity for glucuronidation or glucosidation in N-terminal domain may also be biased by the template used for homology modelling(e.g.…”
Section: Discussionmentioning
confidence: 99%
“…glucuronidation specificity offered by Arg259or glucosidation by UGT2B7) [ 72 ]. However homology modelling successfully implemented to test substrates and inhibitors of other UGT enzymes in the past with a satisfactory level of sensitivity and specificity [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, all members of the UGT 1 and 2 families utilise UDP-GlcUA as a cofactor and hence form glucuronide conjugates. The recent UGT1A6 model reported by Smith et al (2020) showed the presence of Arg256 (equivalent to Arg259 in UGT2B7) in the cofactor binding site (Supplementary Figure S1). However, this residue interacted with the phosphate group of UDP-GlcUA.…”
Section: Molpharm-ar-2020-000104mentioning
confidence: 91%
“…Only two MD simulation studies that investigated ligand binding to UGT proteins (viz. UGT1A6 and UGT1A9/10) have been reported to date (Tripathi et al 2015;Smith et al 2020). Neither of these studies provided experimental verification of residues predicted to be involved in UDP-sugar binding, nor insights into the residues that are essential for cofactor selectivity.…”
Section: Molpharm-ar-2020-000104mentioning
confidence: 98%
See 1 more Smart Citation